1997
DOI: 10.1111/j.1439-0434.1997.tb00406.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential Responses of Guayule (Parthenium argentatum Gray) Genotypes to Culture Filtrate and Toxin from Macrophomina phaseolina (Tassi) Goidanich

Abstract: The potential for using cell-free culture filtrate (CFCF) and toxin (phaseolinone) from Macrophomina phaseolina for rapid and efTective screening procedures for charcoal rot resistance in guayule (Parthenium argentatum) germplasm was assessed. The CFCF and partially purified phaseolinone were incorporated into modified Murashige and Skoog solid medium at the rates of 0-100% (v/v) and 0-1000^g ml"', respectively. The medium pH was adjusted to 5.8 before solidifying with 0.8% agar. Fourweek-old seedlings of 10 g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…2 The fungus is also an important reason for the failure of semiarid agriculture with crops such as guayule. 3 Research on charcoal rot and other plant diseases caused by M. phaseolina has been severely hampered by the unavailability of phaseolinone (1), a phytotoxin believed to play a role in the initial infection of roots, although this role remains to be established experimentally. The phytotoxin from M. phaseolina was first identified by Siddiqui et al 4 in culture filtrates of the fungus and reported by Dhar et al 5 to be 1, an eremophilane sesquiterpenoid, specifically an epoxidized analogue of phomenone.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…2 The fungus is also an important reason for the failure of semiarid agriculture with crops such as guayule. 3 Research on charcoal rot and other plant diseases caused by M. phaseolina has been severely hampered by the unavailability of phaseolinone (1), a phytotoxin believed to play a role in the initial infection of roots, although this role remains to be established experimentally. The phytotoxin from M. phaseolina was first identified by Siddiqui et al 4 in culture filtrates of the fungus and reported by Dhar et al 5 to be 1, an eremophilane sesquiterpenoid, specifically an epoxidized analogue of phomenone.…”
mentioning
confidence: 99%
“…Charcoal rot disease, one of about 500 plant diseases caused by the fungus Macrophomina phaseolina , is responsible for major economic losses to soybean producers in dry years . The fungus is also an important reason for the failure of semiarid agriculture with crops such as guayule . Research on charcoal rot and other plant diseases caused by M. phaseolina has been severely hampered by the unavailability of phaseolinone ( 1 ), a phytotoxin believed to play a role in the initial infection of roots, although this role remains to be established experimentally.…”
mentioning
confidence: 99%
“…Once entered the vascular tissues, fungus plugs the vessels by spreading through the cells (Wyllie, 1998). Enzymatic degradation and toxin production may also lead to charcoal rot (Jones & Wang, 1997; Kuti, Schading, Latigo, & Braford, 1997). M. phaseolina secretes an array of cell wall degrading enzymes which depolymerize the cell wall components such as cellulose, xylan, pectin, polygalacturonic acid and other proteins (Khan et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…An example of the impact of charcoal rot disease on agriculture was provided by attempts to establish commercial natural rubber production with guayule (Parthenium argentatum Gray) in the arid southwest region of the US as an alternative to imported material from the rubber tree (Hevea brasiliensis) [2]. Guayule rubber production was only competitive when plants were grown close enough together that the roots interdigitated, under which conditions charcoal rot could spread from plant to plant destroying the crop [3]. Because charcoal rot is favored by hot, dry conditions [4], it is a climate-impacted plant disease that is predicted to be an increasingly important agronomic problem going forward, given that climate change is predicted to result in hotter, drier conditions in the majority of the world [5].…”
Section: Introductionmentioning
confidence: 99%